Implementación de un sistema web de oferta de productos tradicionales comunitarios, aplicando la metodología dsdm (dinamics systems development method, método de desarrollo de sistemas dinámicos), para la fedomusig (federación de organizaciones de mujeres de Sigchos “Rosita León”), en la provincia de Cotopaxi, Cantón Sigchos - Quindigalle Cuyo, Lidia Yolanda (2014)
Some years ago the trend of offering electronic devices in Ecuador and worldwide has been growing constantly as well as the sale of traditional products by the Federation of Women’s Organizations “Rosita León” in Sigchos, located in Cotopaxi Province, Sigchos Canton, the research analysis allowed us to establish that the market products offered were not adequate and this was the reason why a web system to offer products was developed. This same system was brought about by means of the DSDM methodology (Dynamics Systems Development Method), which allowed us to give coherence, organization and efficiency to the process during the development of the project. Also, tools such as MySQL were used to apply data bases, Joomla for the visual interface and for the content management and also the module OpenCart was used for the electronic store. The principal objective was to develop on efficient software for the commercialization of products and thus allowing the users to visualize the products available, costs and how to buy as well as general information given by means of articles, connections, banners, modules, among other things. The creation of this system allowed the institution and the products for sale to be diffused around the world in this way increasing sales opportunities due to time and cost reduction by eliminating a middleman. The previously mentioned system also increases the speed and precision on sale making available to buyers a wider field of options than traditional business since the can choose from a greater variety that is available 24 hours a day, seven days a week. Finally, the research allowed us to prove our hypothesis by apply interviews and surveys where the need to employ the sales system was verified according to current trends.